(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article examines, on the example of the educational reform in Poland, the general tendencies in reforming the education system of post- socialist countries. Poland is not only a geographic neighbor of Ukraine, but also a country very close to our outlook. In this country, earlier than in Ukraine, reforms in education and society began, and earlier than in Ukraine, the issue of reforming the state system of vocational guidance and counseling became topical. At the moment, the educational system in Poland has a number of additional benefits. Poland’s educational reform was based on the principles of a democratic education system formulated by Polish scholars. The formation of an educational paradigm was based on the choice between adaptive, critical and critical-creative doctrines of education. Implementation of the educational reform in Poland has been expressed, first of all, in the structural reorganization of the whole system of education. The participation of Poland and Ukraine in the Bologna process places educational institutions in the task of effectively integrating certain higher educational institutions and their employees into the implementation and implementation of the main provisions of the Bologna Declaration.